2021
DOI: 10.1007/s11077-021-09418-2
|View full text |Cite
|
Sign up to set email alerts
|

Policy learning as complex contagion: how social networks shape organizational beliefs in forest-based climate change mitigation

Abstract: Policy learning can alter the perceptions of both the seriousness and the causes of a policy problem, thus also altering the perceived need to do something about the problem. This then allows for the informed weighing of different policy options. Taking a social network perspective, we argue that the role of social influence as a driver of policy learning has been overlooked in the literature. Network research has shown that normatively laden belief change is likely to occur through complex contagion—a process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 51 publications
1
18
1
Order By: Relevance
“…Through these various data sources and measures of belief change, we affirm belief reinforcement -and absence of change -as the predominant learning pattern. This pattern commonly appears in adversarial policy subsystems (Funke et al, 2021;Pattison, 2018;Weible, 2008) and contrasts with the theoretical expectations for more cross-coalition learning in collaborative policy subsystems (Gronow et al, 2021;Koebele, 2019;Sandström et al, 2021) or low salient policy subsystems (Giordono, 2020). While our findings largely confirm ACF expectations about the stability of coalitions and beliefs and for learning constraints, we also find important exceptions.…”
Section: Conccontrasting
confidence: 85%
See 1 more Smart Citation
“…Through these various data sources and measures of belief change, we affirm belief reinforcement -and absence of change -as the predominant learning pattern. This pattern commonly appears in adversarial policy subsystems (Funke et al, 2021;Pattison, 2018;Weible, 2008) and contrasts with the theoretical expectations for more cross-coalition learning in collaborative policy subsystems (Gronow et al, 2021;Koebele, 2019;Sandström et al, 2021) or low salient policy subsystems (Giordono, 2020). While our findings largely confirm ACF expectations about the stability of coalitions and beliefs and for learning constraints, we also find important exceptions.…”
Section: Conccontrasting
confidence: 85%
“…These studies largely confirm expectations that coalitions exist in contentious policy subsystems, and these coalitions are generally stable over time (see summary in Weible, Ingold, et al, 2020). Members of advocacy coalitions mainly reveal stability in their policy core beliefs, and when learning, coalition members tend to reinforce their policy core beliefs more than change beliefs, particularly in adversarial policy subsystems (Gronow et al, 2021; Heikkila et al, 2020; Moyson, 2017; Nowlin, 2021; Pattison, 2018; Wagner & Ylä‐Anttila, 2020). The ACF's policy core beliefs refer to broad views about a policy issue, such as general policy positions or problem perceptions (see Jenkins‐Smith et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In focusing on desirable social transitions, geographers have explored how NGOs and retailers can pressure key corporations to agree to zero-deforestation, thereby encouraging transgression of the threshold of acceptability of ecosystem-based climate mitigation across a supply chain 30 . Political scientists have interrogated how improving the diversity and critical mass of influential actors in policy subsystems can improve local acceptability of forest-based climate mitigation 31 . Communication scholars have demonstrated how climate narratives and visuals can strengthen community understanding of longitudinal change, thereby improving feedback between climate-impacted systems and society 32,33 .…”
Section: Perspectivementioning
confidence: 99%
“…Indeed, the ACF argues that policy forums and cross-coalition ties can facilitate such learning. Gronow et al (2021) demonstrated that when multiple social contacts "expose" an actor to beliefs that differ from the actor's own beliefs, this makes it likely that the actor changes their policy beliefs. When applied longitudinally, the ACI can provide insights into the co-evolvement of coordination and beliefs.…”
Section: F I G U R E 5 (Continued)mentioning
confidence: 99%